Identifying six single nucleotide variants in the COL17A1 gene that alter RNA splicing: database analysis and minigene assays - Yingfei Shao; Ran Zhang (Scientific Reports)
Abstract Collagen type XVII alpha 1 chain (COL17A1) is a protein in the collagen family crucial for maintaining the integrity of skin and epithelial tissues. It is also vital for enamel formation and plays a significant role in the differentiation of ameloblasts. Many studies have indicated that single nucleotide variants (SNVs) can disrupt normal splicing process of the pre-mRNA by altering various splicing regulatory signals. This study aimed to explore the potential impact of SNVs in COL17A1 geneon splicing events, with the ultimate aim of improving the prediction of disease prognosis. Here, we analyzed 703 SNVs including 446 exonic variants and 257 intronic variants in the COL17A1 gene using bioinformatics tools and identified candidate variants that may induce splicing alterations via minigene assays. Our study identified that, among eight candidate variants, six variants (c.1139 C > T, c.1834G > A, c.3198 C > T, c.202 + 6T > G, c.1222 + 4 A > G, c.3071-5G > A) induced splicing alterations by interfering with the recognition of classical splice sites or disrupting the ratio of exonic splicing enhancers/exonic splicing silencers, or both. This study emphasizes the necessity of assessing the effects of SNVs on at the mRNA level, aiding accurate characterization of COL17A1 variants and enabling the development of personalized treatment options.